2015
DOI: 10.1161/atvbaha.114.304764
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nonatheromatous Lesions in Peripheral Arterial Disease

Abstract: Objective-The histopathology of peripheral arterial disease and the accompanying calcification are poorly defined, and it is not known whether this varies according to different risk factors. Approach and Results-Sections from 176 upper and lower leg arteries were examined histologically in specimens from amputations of 60 patients with peripheral arterial disease, of whom 58% had diabetes mellitus, 35% had end-stage renal disease, and 48% had a history of smoking. The most common findings were calcification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 30 publications
1
71
1
1
Order By: Relevance
“…(17) Interestingly, we found that age, male sex, tobacco use, and diabetes maintained their association with tibial calcium even after adjusting for presence of PAD. This may reflect the more medial localization of calcification in the tibial vessels or the relatively higher proportion of non-atheromatous lesions recently reported by O’Neill et al(18) It also is possible that atherosclerosis and calcification share overlapping risk factors. This would support the concept that tibial calcification independently contributes to limb ischemia and poor outcomes; however the mechanisms behind these associations have not been identified.…”
Section: Discussionmentioning
confidence: 89%
“…(17) Interestingly, we found that age, male sex, tobacco use, and diabetes maintained their association with tibial calcium even after adjusting for presence of PAD. This may reflect the more medial localization of calcification in the tibial vessels or the relatively higher proportion of non-atheromatous lesions recently reported by O’Neill et al(18) It also is possible that atherosclerosis and calcification share overlapping risk factors. This would support the concept that tibial calcification independently contributes to limb ischemia and poor outcomes; however the mechanisms behind these associations have not been identified.…”
Section: Discussionmentioning
confidence: 89%
“…In a study examining breast arterial calcification (BAC) in women with CKD, BAC was found exclusively in the media, was associated with peripheral arterial calcification, and was found to be a marker of generalized medial arterial calcification (MAC), a histologic finding common in amputated limbs. 34 In a follow-up study, BAC was independently associated with new PAD events in women with ESRD. 35 As these analyses did not include men, it is unknown if these histologic correlates indicate increased PAD risk in women, but they show that women with CKD have more MAC, and that MAC may be associated with a more accelerated form of PAD.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report on the histopathological assessment of PAD (176 upper and lower leg artery specimens) patients highlights that the most common observations were medial calcification (present in 72% of arteries examined) and intimal thickening without lipid (present in 68% of arteries examined). Classical atherosclerosis was only identified in 23% of arteries [139]. Non-atheromatous intimal thickening was frequently observed, resulting in complete occlusion in some vessels.…”
Section: Potential Biomarkers For Padmentioning
confidence: 99%